(untitled) (Journal of Plant Disease Sciences, 2017)
Chickpea ( L.) one of Cicer arietinum the most important pulse crops grown in Asian subcontinent, third most important food legume of the world. Maharashtra contributes about 10 per cent share in total production of country. One of the major production constraints in chickpea is wilt Fusarium caused by f.sp Fusarium oxysporum . ciceri (Jalali and Chand, 1992). The disease is wide spread in chickpea growing areas of the world and is reported from 33 countries The pathogen penetrates the roots and provokes either root rots or tracheomycosis when they invade the vascular system, causing wilt disease. The disease can be observed in susceptible cultivar within 25 days after sowing in infected soil and this known as ’early wilt’ (Haware 1980). Wilting may et al., also occur during reproductive growth and is known as ’late wilt’. Fusarium oxysporum f.sp. is highly variable pathogen. ciceri The present study was conducted to understand the cultural and morphological variability among isolates of f.sp. Fusarium oxysporum ciceri, collected from different locations of Maharashtra.